3,5-Diiodothyronine: A Novel Thyroid Hormone Metabolite and Potent Modulator of Energy Metabolism - Senese, Rosalba; de Lange, Pieter; Petito, Giuseppe; Moreno, Maria; Goglia, Fernando; Lanni, Antonia (Frontiers in Endocrinology, 2018)
Over thirty years of research has demonstrated that 3,5-diiodo-L-thyronine (3,5-T2), an endogenous metabolite of thyroid hormones, exhibits interesting metabolic activities. In rodent models, exogenously administered 3,5-T2 rapidly increases resting metabolic rate and elicits short-term beneficial hypolipidemic effects; however, very few studies have evaluated the effects of endogenous and exogenous T2 in humans. Further analyses on larger cohorts are needed to determine whether 3,5-T2 is a potent additional modulator of energy metabolism. In addition, while several lines of evidence suggest that 3,5-T2 mainly acts through Thyroid hormone receptors (THRs)- independent ways, with mitochondria as a likely cellular target, THRs-mediated actions have also been described. The detailed cellular and molecular mechanisms through which 3,5-T2 elicits a multiplicity of actions remains unknown. Here, we provide an overview of the most recent literature on 3,5-T2 bioactivity with a particular focus on short-term and long-term effects, describing data obtained through in vivo and in vitro approaches in both mammalian and non-mammalian species.